Food Microstructures : Microscopy, Measurement And Modelling. - Morris, V. J.; Groves, K.; ScienceDirect eBooks (Burlington : Elsevier Science, 2013)
The development of high-quality foods with desirable properties for both consumers and the food industry requires a comprehensive understanding of food systems and the control and rational design of food microstructures. Food microstructures reviews best practice and new developments in the determination of food microstructure. After a general introduction, chapters in part one review the principles and applications of various spectroscopy, tomography and microscopy techniques for revealing food microstructure, including nuclear magnetic resonance (NMR) methods, environmental scanning.
6 Fourier transform infrared (FTIR) and Raman microscopy: principles and applications to food microstructures6.1 Introduction; 6.2 Instrumentation; 6.3 Data analysis; 6.4 Applications; 6.5 Conclusion and future trends; 6.6 Sources of further information and advice; 6.7 References; 7 Ultrasonic and acoustic microscopy: principles and applications to food microstructures; 7.1 Introduction; 7.2 Theories of ultrasound propagation; 7.3 Construction of an acoustic microscope; 7.4 Operation and calibration of an acoustic microscope.
Print version record.
7.5 Exemplars of acoustic microscopy and applications to food structure.
Elsevier
Keywords: Food -- Composition; Food -- Analysis; Microstructure; TECHNOLOGY & ENGINEERING -- Food Science; Food -- Analysis; Food -- Composition; Microstructure; Electronic books